The silence that speaks [large type] - Kane, Andrea (Kane, Andrea. Forensic Instincts novel, 2015)
Former Navy SEAL Marc Deveraux teams up with Forensic Instincts to protect the life of nurse and former flame Madeline Westfield, whose would-be killer blames her for the death of a hospital administrator.